Coal-based hard carbon negative electrode material and preparation method thereof
By using coal with high volatile content and introducing compounds such as CaS and Fe2P, the specific surface area of coal-based hard carbon anode materials is regulated, and the problems of high cost and unstable source of existing sodium ion battery anode materials are solved, and the development of high-efficiency and low-cost sodium ion battery anode materials are achieved.
Patent Information
- Application Number
- CN202411868993.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
AI Technical Summary
The existing sodium ion battery negative electrode materials have problems such as high cost and unstable source, which is difficult to meet the needs of commercial applications.
Coal with high volatile content is used as raw materials, and the electrochemical performance of coal-based hard carbon anode materials is synergistically improved by regulating the specific surface area and introducing compounds such as CaS and Fe2P.
The obtained coal-based hard carbon anode material has higher capacity and first effect, low cost, wide application range, better economical and application prospects.
Smart Images

Figure BDA0005195273830000111 
Figure BDA0005195273830000121 
Figure HDA0005195273840000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a coal-based hard carbon negative electrode material and a preparation method thereof. Background Art
[0002] With the continuous growth of global energy demand and the increasing concern for environmental sustainability, it is particularly important to develop efficient, low-cost and environmentally friendly energy storage technologies. Lithium-ion batteries have been widely used in portable electronic devices, electric vehicles and other fields due to their advantages such as high energy density and long cycle life. However, the limited and uneven distribution of lithium resources have led to rising costs and supply security issues for lithium-ion batteries. Therefore, finding alternative energy storage solutions has become an urgent need.
[0003] Sodium-ion batteries have received widespread attention as a potential alternative. Compared with lithium, sodium is abundant and widely distributed in the earth's crust, and its cost is low, which makes large-scale energy storage applications possible. However, to achieve the commercialization of sodium-ion batteries, a series of technical challenges need to be overcome, the most critical of which is the development of high-performance negative electrode materials. Ideal sodium-ion battery negative electrode materials should have high specific capacity, good rate performance and stable cycle life.
[0004] In recent years, researchers have explored various types of carbon-based materials as negative electrodes for sodium-ion batteries, including hard carbon, soft carbon, and graphene. Although these materials have shown certain application potential, they still have problems such as high cost and unstable sources. In this context, the use of naturally abundant coal resources to prepare negative electrode materials for sodium-ion batteries has gradually become a new research hotspot.
[0005] Coal is a complex organic mineral with unique microstructural features, such as a developed pore system and a high carbon content. These properties make coal, especially bituminous coal, the most common commercial coal, an efficient electrochemical energy storage material after proper treatment. However, untreated bituminous coal materials usually exhibit poor electrochemical properties, which limits their direct application in sodium-ion batteries. Therefore, modifying them by physical and chemical means to improve their electrochemical properties has become one of the main research directions.
[0006] It is based on this background that the present invention proposes a new type of coal-based high-capacity sodium ion battery negative electrode material and a preparation method thereof, aiming to solve the above-mentioned problems and provide an economical and effective sodium ion battery negative electrode material selection. Summary of the invention
[0007] In view of the above-mentioned problems of the prior art, the present invention adopts coal with a high volatile matter content as raw material, regulates the specific surface area of the product, and introduces compounds of specific types and contents into the product through the conversion of ash elements, thereby achieving a synergistic improvement in the electrochemical performance of coal-based hard carbon negative electrode materials.
[0008] The present invention first provides a coal-based hard carbon negative electrode material, using coal as a raw material, and the specific surface area of the coal-based hard carbon negative electrode material is less than 50m 2 / g, and the coal-based hard carbon negative electrode material contains CaS and Fe2P, and the mass content m1 of CaS in the coal-based hard carbon negative electrode material and the mass content m2 of Fe2P in the coal-based hard carbon negative electrode material satisfy 0<m1+m2≤5%.
[0009] As some preferred solutions, the ash content of the coal used as raw material is ≥5%. The coal used as raw material can be selected from one or more of bituminous coal, sub-bituminous coal and the like.
[0010] As some preferred solutions, the volatile matter content of the coal used as raw material is ≥25%.
[0011] As some preferred solutions, the specific surface area of coal-based hard carbon negative electrode materials is less than 40m 2 / g, and <35m 2 / g is better, 5m 2 / g<Specific surface area<30m 2 / g is further improved, with 10m 2 / g<Specific surface area<20m 2 / g is optimal.
[0012] As some preferred schemes, the mass content m1 of CaS in the coal-based hard carbon negative electrode material and the mass content m2 of Fe2P in the coal-based hard carbon negative electrode material respectively satisfy 0.01%<m1<0.2%, 0.001%<m2<0.15%, and further preferably satisfy 0.01%<m1<0.035%, 0.001%<m2<0.05%, respectively.
[0013] As some preferred schemes, in the coal-based hard carbon negative electrode material, the element content Ca shown by ICP is 100-1500ppm, Fe is 100-3000ppm, S is 100-800ppm, and P is 10-1500ppm; further preferably, the element content Ca shown by ICP is 400-800ppm, Fe is 800-2000ppm, S is 200-400ppm, and P is 250-700ppm.
[0014] As some preferred schemes, the first-week reversible capacity of coal-based hard carbon negative electrode materials can reach more than 290 mAh / g, and the first-week coulombic efficiency can reach more than 75%; further preferably, the first-week reversible capacity can reach more than 300 mAh / g or more than 310 mAh / g, and the first-week coulombic efficiency can reach more than 80% or more than 83%.
[0015] The present invention also provides a method for preparing the coal-based hard carbon negative electrode material, comprising the steps of sequentially subjecting the coal raw material to acid treatment, pre-carbonization, steam activation, and secondary carbonization; the pre-carbonization is performed at 700-900°C, and the specific surface area of the material after pre-carbonization is controlled to be greater than 100m 2 / g; after steam activation, the specific surface area of the controlled material increases by 150m 2 / g or more; in the second carbonization process, conversion sources that form CaS and Fe2P with the residual elements are introduced, and the coal-based hard carbon negative electrode material is obtained by carbonization treatment above 1200°C.
[0016] As some preferred schemes, the particle size of the acid-treated coal raw material is Dv50=0.1-20μm, preferably, the particle size is Dv50=1-10μm.
[0017] As some preferred schemes, the reagent for acid treatment is selected from one or more of hydrochloric acid, nitric acid, and hydrofluoric acid, and is further preferably a mixed reagent of the three, and the volume ratio of the three is further preferably 3:2:5.
[0018] As some preferred schemes, the heating rate of pre-carbonization is 1-10℃ / min; the holding time of pre-carbonization is 1-48h; steam-activated water vapor is used as an activating agent; the temperature of steam activation is 700-900℃; the heating rate of the second carbonization is 1-10℃ / min; and the holding time is 2-48h.
[0019] As some preferred solutions, the specific surface area of the material after steam activation is controlled to be > 400m 2 / g, further>500m 2 / g.
[0020] As some preferred schemes, the conversion source in the second carbonization includes one or more of a phosphorus source and a sulfur source, preferably NaH2PO2·H2O.
[0021] The present invention also provides application of the above-mentioned coal-based hard carbon negative electrode material in sodium ion batteries.
[0022] Compared with the prior art, the present invention has at least the following beneficial effects:
[0023] The present invention breaks through the traditional method of using coal as raw material, pursues a treatment method for fully removing ash, selects coal raw materials with higher ash and volatile matter contents, converts part of the remaining ash elements into CaS and Fe2P which are more conducive to the performance of hard carbon materials, and coordinately regulates the pore-forming process to obtain a suitable specific surface area. The obtained coal-based hard carbon negative electrode material has higher capacity and first effect, broadens the application scope of coal raw materials, has better economy and better application prospects in sodium ion batteries.
[0024] In the preparation method of the present invention, the selection of raw materials, acid treatment and effective regulation of the change in specific surface area during the two carbonization processes are combined to cause the pore network to produce suitable change paths such as promotion, cross-linking, expansion, and reconstruction, and ultimately obtain a product with a stable pore network structure that is conducive to ion transmission. At the same time, during the preparation process, by introducing a conversion source, the effective conversion of CaS and Fe2P in the product is further regulated, the target product is successfully obtained, and the synergistic improvement of related electrochemical properties is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 These are the XRD diagrams of Examples 1-1, 2-1, 3-1, 4-1, and 5-1 of the present invention.
[0027] Figure 2 It is the first-week charge and discharge curve diagram of Examples 1-1, 2-1, 3-1, 4-1, and 5-1 of the present invention.
[0028] Figure 3 It is the charge and discharge curve diagram of comparative examples 1-1 and 2-1 of the present invention.
[0029] Figure 4 These are the XRD diagrams of comparative examples 1-1 and 2-1 of the present invention. DETAILED DESCRIPTION
[0030] The present invention uses coal as the raw material for the hard carbon negative electrode. Bituminous coal raw materials often introduce a large amount of ash during the mining process, and too high ash will affect the preparation process and electrochemical performance of the battery. It is necessary to use means such as impurity removal, modification, and conversion to eliminate the negative effects of ash. The ash content and type of coal raw materials from different sources or batches also vary. The total ash content generally ranges from 0.1% to 15%. The components in the ash include but are not limited to one or more of SiO2, CaO, CaCO3, FeS2, Al2O3, Fe2O3, MgO, and Cr2O3. Among them, the components with the largest content are mainly compounds containing Fe, Ca, Si, and S (oxides, sulfides, or carbonate compounds, etc.). In addition, there are also more volatiles in the coal raw materials, and the content generally ranges from 5% to 60%, which is an important source of pore structure in the process of preparing hard carbon negative electrodes. In the present invention, unless otherwise specified, the content mentioned refers to the mass content.
[0031] In order to improve the performance of the hard carbon negative electrode, unlike the previous operation methods of using coal with relatively low ash and volatile matter as raw materials and pursuing lower ash residue after impurity removal as the main goal, the present invention does not limit the ash and volatile matter content of the coal raw materials. All existing coal materials can be used as raw materials, and in particular, bituminous coal with higher ash and volatile matter can be selected as coal raw materials, preferably with an ash content of ≥5% and a volatile matter content of ≥25%. Higher volatile matter brings higher initial porosity, and can also be reduced to a stable target pore structure through the pore reforming process optimized by the present invention to achieve a smaller specific surface area. After the ash is removed to a certain extent, the present invention retains an appropriate amount of ash residue and converts it into CaS and Fe2P that are more conducive to the performance of the hard carbon material, thereby improving the embedding ability of the hard carbon negative electrode material for sodium ions. At the same time, appropriate pore-forming means are used to enable the volatile matter to construct more stable cross-linked pore networks and improve the transmission capacity for sodium ions, thereby achieving the purpose of synergistically improving the electrochemical performance of the hard carbon negative electrode material.
[0032] In the first aspect, the present invention provides a coal-based hard carbon negative electrode material, using coal as a raw material, and the specific surface area of the coal-based hard carbon negative electrode material is less than 50m 2 / g, and the coal-based hard carbon negative electrode material contains CaS and Fe2P, and the mass content m1 of CaS in the coal-based hard carbon negative electrode material and the mass content m2 of Fe2P in the coal-based hard carbon negative electrode material satisfy 0<m1+m2≤5%.
[0033] The applicant found that after the ash in the coal raw material is removed, a part of Fe, Ca, Si, and S compounds can be retained. These compounds can be converted into the target products CaS and Fe2P by introducing an appropriate amount of conversion source (such as a phosphorus source) and combining it with appropriate carbonization treatment. The two convert the existence form of these elements into a structural form and ratio relationship that is conducive to capacity improvement. At the same time, appropriate carbonization treatment is also conducive to avoiding the problem of unstable pore structure caused by a higher volatile content, and maintaining the specific surface area of the final product to 50m 2 / g or less to achieve synergistic optimization of performance.
[0034] As some preferred examples, the specific surface area of coal-based hard carbon negative electrode materials is less than 40 m 2 / g, and <35m 2 / g is better, 5m 2 / g<Specific surface area<30m 2 / g is further improved, with 10m 2 / g<Specific surface area<20m 2 The limited specific surface area optimizes the degree of reconstruction of the pore structure by volatiles, which is conducive to the stable performance of capacity and first effect.
[0035] As some preferred examples, in the coal-based hard carbon negative electrode material, the mass content m1 of CaS in the coal-based hard carbon negative electrode material and the mass content m2 of Fe2P in the coal-based hard carbon negative electrode material respectively satisfy 0.01%<m1<0.2%, 0.001%<m2<0.15%, and further preferably satisfy 0.01%<m1<0.035%, 0.001%<m2<0.05%, respectively.
[0036] As some preferred examples, in the coal-based hard carbon negative electrode material, the element content of Ca shown by ICP is 100-1500ppm, Fe is 100-3000ppm, S is 100-800ppm, and P is 10-1500ppm; further, the element content of Ca shown by ICP is 400-800ppm, Fe is 800-2000ppm, S is 200-400ppm, and P is 250-700ppm. Among them, 1000ppm corresponds to a mass content of 0.1%. The optimized element range provides optimized CaS and Fe2P contents and appropriate corresponding element contents in other forms.
[0037] The above-mentioned coal-based hard carbon negative electrode material provided by the present invention has a first-week reversible capacity of more than 290 mAh / g, a first-week coulombic efficiency of more than 75%, and in an optimized scheme, a first-week reversible capacity of more than 300 mAh / g or more than 310 mAh / g, and a first-week coulombic efficiency of more than 80% or more than 83%. The coal-based hard carbon negative electrode material of the present invention can be used as a negative electrode active material and has good application prospects in sodium ion batteries.
[0038] In the above-mentioned sodium ion battery, the construction of other materials and systems is not particularly limited and can be implemented within the scope of general designs that have been successfully implemented in the field. In addition, if there is no conflict, the designs in the above-mentioned different sodium ion batteries can also be cross- or superimposed.
[0039] The sodium ion battery also includes a positive electrode, a separator and an electrolyte. As some non-limiting examples, the positive electrode material may include layered transition metal oxides, such as sodium iron manganate, sodium iron titanate, etc., polyanionic compounds, such as olivine sodium iron phosphate, sodium iron sulfate, etc., Prussian blue compounds, such as Na4Fe(CN)6, NaFe(CN)6, etc.
[0040] In a second aspect, the present invention also provides a method for preparing the coal-based hard carbon negative electrode material, comprising the steps of acid treatment, pre-carbonization, steam activation, and secondary carbonization of the coal raw material in sequence; the pre-carbonization is carried out at 700-900°C, and the specific surface area of the material after pre-carbonization is controlled to be greater than 100m 2 / g; after steam activation, the specific surface area of the controlled material increases by 150m 2 / g or more; in the second carbonization process, conversion sources that form CaS and Fe2P with the residual elements are introduced, and the coal-based hard carbon negative electrode material is obtained by carbonization treatment above 1200°C.
[0041] In the above method, the acid treatment process removes most of the ash and can introduce a large number of active groups to build more cross-linked structures, which is conducive to the generation of more pores in the subsequent two carbonization processes. Pre-carbonization produces semi-coke materials with high carbon content and certain pore structure. The pre-carbonization process controls the initial formation of cross-linked pore structure (specific surface area> 100m 2 / g), providing a stable basis for the subsequent cross-linking and transformation of pores. During the steam activation process, steam and carbon react chemically, causing some carbon atoms to be removed, leaving gaps, thereby forming pores inside the semi-coke material. As the reaction proceeds, the pores gradually expand and connect to form a complex pore network. The pores are further controlled (lifted 150m 2 / g or more) can be steadily increased, and prepare for the reconstruction of pores and the stable reduction of specific surface area during the second carbonization. In addition to sufficient carbonization and the formation of a stable pore network in the second carbonization, the addition of conversion sources effectively generates a controllable amount of CaS and Fe2P, achieving the optimization and improvement of material performance.
[0042] In the above method, the content of CaS and Fe2P and the content of each element therein can be controlled by regulating the conditions of the preparation method. First, the coal raw material generally contains a sufficient content of the components containing the above elements. Then, during the acid treatment process, it is easy to obtain a material with a target residual amount by selecting a suitable acid treatment reagent, ratio, time, temperature and other conditions. Finally, the amount of conversion source added can be controlled to obtain the target conversion amount of CaS and Fe2P. The selection of the control means and conditions belongs to conventional technical means and is easy to achieve.
[0043] As some preferred examples, the particle size of the acid-treated coal raw material can be controlled at Dv50 = 0.1-20 μm, which is conducive to the full acid treatment and the appropriate particle size to build the contact holes of the hard carbon negative electrode. Further preferably, it is controlled at Dv50 = 1-10 μm, such as 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm.
[0044] As some preferred examples, the acid treatment reagent is selected from one or more of hydrochloric acid, nitric acid, and hydrofluoric acid, preferably a mixed reagent of the three, and the volume ratio of the three is further preferably 3:2:5. The mixed reagent is conducive to introducing multiple types of active oxygen-containing functional groups such as carboxyl (-COOH), hydroxyl (-OH), lactone (-COOR) and carbonyl (=O) into the material, promoting the diversified formation of the cross-linked network.
[0045] As some preferred examples, after the acid treatment, the material is further washed and dried to remove the residual acid solution and prepare for pre-carbonization.
[0046] As some preferred examples, the heating rate can be optimized during pre-carbonization to allow the volatile matter to volatilize stably, and the heating rate can be 1-10°C / min; the pre-carbonization insulation time can also be selected as needed, and is generally preferably 1-48h.
[0047] As some preferred examples, steam activation generally uses water vapor as an activator, and other activators that do not cause side reactions can also be used. The temperature of steam activation is preferably 700-900°C, and the activation time can also be selected as needed to obtain the target specific surface area increase. Further preferably, the specific surface area of the material after steam activation is controlled to be >400m 2 / g, further>500m 2 / g is optimal.
[0048] As some preferred examples, the conversion sources in the second carbonization include phosphorus sources, sulfur sources, etc. In general, the residual Fe, Ca, and S in the material ash can meet the needs of the conversion amount. The phosphorus source can be introduced alone to promote the conversion of Fe into Fe2P while releasing part of S and forming CaS. Sodium hypophosphite (NaH2PO2·H2O) is the best phosphorus source, which has higher conversion reaction activity in the second carbonization.
[0049] As some preferred examples, the heating rate can also be optimized during the second carbonization to promote complete carbonization and pore structure reconstruction. The heating rate can be 1-10°C / min, and the holding time can also be selected as needed, generally 2-48h is preferred.
[0050] The embodiments of the present invention are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those of ordinary skill in the art without making creative work belong to the scope of protection of the present application. The chemical raw materials involved in the embodiments of the present invention are all prior art and are commercially available. The experimental devices, test devices, etc. involved in the following examples and comparative examples are all conventional devices in the art, without special requirements and restrictions.
[0051] The present invention is further described in detail below through specific examples. The examples of the present invention adopt a grouping form, with coal raw materials from different sources forming one group, and five sample materials from different batches are selected in each group of examples.
[0052] Embodiments 1-1 to 1-5:
[0053] (1) The bituminous coal raw material particles are crushed to a particle size of Dv50 = 5 μm. After testing, the ash content of the bituminous coal raw material is about 8.9% and the volatile matter is about 35.7%.
[0054] (2) using hydrochloric acid, nitric acid, and hydrofluoric acid in a volume ratio of 3:2:5 to prepare a solution, and then mixing it with the crushed raw material for acid washing and purification, washing the acid-washed and purified material with water and filtering it until the pH is 7, and drying the filtered material.
[0055] (3) The dried material was carbonized for the first time at 700°C under nitrogen atmosphere protection, with a heating rate of 3°C / min and kept at 700°C for 3h.
[0056] (4) Activate the pre-carbonized material using water vapor as an activating agent at 700°C for 2 hours, with a discharge temperature of 50°C.
[0057] (5) The activated material was subjected to a second carbonization treatment by adding 5 g of NaH2PO2·H2O. Under the protection of inert gas, the heating rate was 3°C / min and the temperature was kept at 1300°C for 3 h to obtain a coal-based hard carbon material.
[0058] Embodiment 2-1~2-5:
[0059] (1) The bituminous coal raw material particles are crushed to a particle size of Dv50 = 5 μm. After testing, the ash content of the bituminous coal raw material is about 8.1%, and the volatile matter is about 36.3%.
[0060] (2) using hydrochloric acid, nitric acid, and hydrofluoric acid in a volume ratio of 3:2:5 to prepare a solution, and then mixing it with the crushed raw material for acid washing and purification, washing the acid-washed and purified material with water and filtering it until the pH is 7, and drying the filtered material.
[0061] (3) The dried material was carbonized for the first time at 700°C under nitrogen atmosphere protection, with a heating rate of 3°C / min and kept at 700°C for 3h.
[0062] (4) Activate the pre-carbonized material using water vapor as an activating agent at 700°C for 2 hours, with a discharge temperature of 50°C.
[0063] (5) The activated material was subjected to a second carbonization treatment by adding 0.1 g of NaH2PO2·H2O. Under the protection of inert gas, the heating rate was 3°C / min and the temperature was kept at 1300°C for 3 h to obtain a coal-based hard carbon material.
[0064] Embodiment 3-1~3-5:
[0065] (1) The bituminous coal raw material particles are crushed to a particle size of Dv50 = 5 μm. After testing, the ash content of the bituminous coal raw material is about 9.3%, and the volatile matter is about 33.6%.
[0066] (2) using hydrochloric acid, nitric acid, and hydrofluoric acid in a volume ratio of 3:2:5 to prepare a solution, and then mixing it with the crushed raw material for acid washing and purification, washing the acid-washed and purified material with water and filtering it until the pH is 7, and drying the filtered material.
[0067] (3) The dried material was carbonized for the first time at 700°C under nitrogen atmosphere protection, with a heating rate of 3°C / min and kept at 700°C for 3h.
[0068] (4) Activate the pre-carbonized material using water vapor as an activating agent at 700°C for 2 hours, with a discharge temperature of 50°C.
[0069] (5) The activated material was subjected to a second carbonization treatment by adding 10 g of NaH2PO2·H2O. Under the protection of inert gas, the heating rate was 3°C / min and the temperature was kept at 1300°C for 3 h to obtain a coal-based hard carbon material.
[0070] Embodiments 4-1 to 4-5:
[0071] (1) The bituminous coal raw material particles are crushed to a particle size of Dv50 = 5 μm. After testing, the ash content of the bituminous coal raw material is about 8.7%, and the volatile matter is about 34.4%.
[0072] (2) using hydrochloric acid, nitric acid, and hydrofluoric acid in a volume ratio of 3:2:5 to prepare a solution, and then mixing it with the crushed raw material for acid washing and purification, washing the acid-washed and purified material with water and filtering it until the pH is 7, and drying the filtered material.
[0073] (3) The dried material was carbonized at 800 °C for the first time under nitrogen atmosphere protection, with a heating rate of 3 °C / min and kept at 800 °C for 3 h.
[0074] (4) Activate the pre-carbonized material using water vapor as an activating agent at 700°C for 2 hours, with a discharge temperature of 50°C.
[0075] (5) The activated material was subjected to a second carbonization treatment by adding 5 g of NaH2PO2·H2O. Under the protection of inert gas, the heating rate was 3°C / min and the temperature was kept at 1300°C for 3 h to obtain a coal-based hard carbon material.
[0076] Embodiment 5-1~5-5:
[0077] (1) The bituminous coal raw material particles are crushed to a particle size of Dv50 = 5 μm. After testing, the ash content of the bituminous coal raw material is about 8.9% and the volatile matter is about 31.5%.
[0078] (2) using hydrochloric acid, nitric acid, and hydrofluoric acid in a volume ratio of 3:2:5 to prepare a solution, and then mixing it with the crushed raw material for acid washing and purification, washing the acid-washed and purified material with water and filtering it until the pH is 7, and drying the filtered material.
[0079] (3) The dried material was carbonized for the first time at 900 °C under nitrogen atmosphere protection, with a heating rate of 3 °C / min and kept at 800 °C for 3 h.
[0080] (4) Activate the pre-carbonized material using water vapor as an activating agent at 700°C for 2 hours, with a discharge temperature of 50°C.
[0081] (5) The activated material was subjected to a second carbonization treatment by adding 5 g of NaH2PO2·H2O. Under the protection of inert gas, the heating rate was 3°C / min and the temperature was kept at 1300°C for 3 h to obtain a coal-based hard carbon material.
[0082] Comparative Example 1
[0083] (1) The bituminous coal raw material particles are crushed to a particle size of Dv50 = 5 μm. After testing, the ash content of the bituminous coal raw material is about 8.9% and the volatile matter is about 35.7%.
[0084] (2) using hydrochloric acid, nitric acid, and hydrofluoric acid to mix in a volume ratio of 1:1:3 to prepare a solution, and then mixing it with the crushed raw material for acid washing and purification, washing the acid-washed and purified material with water and filtering until the pH is 7, and drying the filtered material.
[0085] (3) The dried material was carbonized for the first time at 700°C under nitrogen atmosphere protection, with a heating rate of 3°C / min and kept at 700°C for 3h.
[0086] (4) Activate the pre-carbonized material using water vapor as an activating agent at 700°C for 2 hours, with a discharge temperature of 50°C.
[0087] (5) The activated material was subjected to a second carbonization treatment by adding 20 g of NaH2PO2·H2O. Under the protection of inert gas, the heating rate was 3°C / min and the temperature was kept at 1300°C for 3 h to obtain a coal-based hard carbon material.
[0088] Comparative Example 2
[0089] (1) The bituminous coal raw material particles are crushed to a particle size of Dv50 = 5 μm. After testing, the ash content of the bituminous coal raw material is about 8.9% and the volatile matter is about 31.5%.
[0090] (2) using hydrochloric acid, nitric acid, and hydrofluoric acid in a volume ratio of 3:2:5 to prepare a solution, and then mixing it with the crushed raw material for acid washing and purification, washing the acid-washed and purified material with water and filtering it until the pH is 7, and drying the filtered material.
[0091] (3) The dried material was carbonized for the first time at 700°C under nitrogen atmosphere protection, with a heating rate of 3°C / min and kept at 700°C for 3h.
[0092] (4) Activate the pre-carbonized material using water vapor as an activating agent at 900°C for 2 hours, with a discharge temperature of 50°C.
[0093] (5) The activated material was subjected to a second carbonization treatment by adding 5 g of NaH2PO2·H2O. Under the protection of inert gas, the heating rate was 3°C / min and the temperature was kept at 1300°C for 3 h to obtain a coal-based hard carbon material.
[0094] The hard carbon materials prepared by the above method were subjected to ICP element content detection and XRD diffraction analysis, and assembled into sodium buckle batteries for electrochemical performance testing to obtain the first-week reversible capacity and first-week coulombic efficiency performance indicators. The test results are listed in Table 1 and the attached figure.
[0095] Table 1
[0096]
[0097]
[0098] It can be seen from the embodiments and comparative examples of the present invention that by changing the parameters in the preparation method through the method of the present invention, a coal-based hard carbon negative electrode material with controllable specific surface area and CaS and Fe2P content can be obtained, and the first-week reversible capacity of the material can reach more than 290mAh / g, and the first-week coulomb efficiency can reach more than 75%. Among them, the change in specific surface area during the preparation process reflects the process that the pore structure in the coal raw material is formed by the volatilization of volatiles, and then promoted, cross-linked, expanded, and reconstructed during acid treatment and two carbonization processes. The final pore structure is stable and conducive to ion transmission. At the same time, the effective amount conversion of CaS and Fe2P and the control of element content further contribute to the capacity of the material.
[0099] like Figure 1-2 As shown, in each embodiment of the present invention, controlled amounts of CaS and Fe2P are formed, and the charge-discharge curves show good electrical properties. Figure 3-4 As shown, in comparative example 1-1, due to the milder treatment conditions and the addition of more conversion sources, excessive CaS and Fe2P were retained, and XRD showed that the sum of the two contents exceeded 5%, resulting in a significant reduction in electrochemical performance. The specific surface area of comparative example 2-1 after steam activation was not increased enough, which affected the reconstruction path of the pores and the pore stability, and the electrochemical performance was not improved.
[0100] Compared with Example 5, it can be seen from Examples 1-4 that the change control of the specific surface area during the preparation process has a significant impact on the initial effect of the material. The increase in the specific surface area of the material after steam activation will affect the reconstruction of the pore network, thereby affecting the kinetics of ion insertion and extraction. The specific surface area of the material after steam activation is increased to >400m 2 / g, even>500m 2 / g is conducive to further improving the first-effect performance.
[0101] Compared with Examples 2-4, it can be seen from Example 1 that the optimized element content is conducive to further improving the comprehensive performance of capacity and first efficiency. When the element content is 400-800ppm for Ca, 800-2000ppm for Fe, 200-400ppm for S, and 250-700ppm for P (Example 1), the first-week reversible capacity of the material can reach more than 310mAh / g, and the first-week coulombic efficiency can reach more than 83%.
[0102] The technical features of the above-described embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above-described embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. Although the embodiments of the present invention have been shown and described above, it can be understood that the above-described embodiments are exemplary and cannot be understood as limitations of the present invention. Those of ordinary skill in the art can change, modify, replace and deform the above-described embodiments within the scope of the present invention. In addition, those of ordinary skill in the art can combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples without contradiction.
Claims
1. A coal-based hard carbon negative electrode material, using coal as raw material, the specific surface area of the coal-based hard carbon negative electrode material is less than 50m 2 / g, and the coal-based hard carbon negative electrode material contains CaS and Fe2P, and the mass content m1 of CaS in the coal-based hard carbon negative electrode material and the mass content m2 of Fe2P in the coal-based hard carbon negative electrode material satisfy 0<m1+m2≤5%.
2. The coal-based hard carbon negative electrode material according to claim 1, characterized in that: The ash content of the coal used as raw material is ≥5%, and the volatile matter content is ≥25%.
3. The coal-based hard carbon negative electrode material according to claim 1, characterized in that: The specific surface area of coal-based hard carbon negative electrode materials is less than 40m 2 / g, and <35m 2 / g is better, 5m 2 / g<Specific surface area<30m 2 / g is further improved, with 10m 2 / g<Specific surface area<20m 2 / g is optimal.
4. The coal-based hard carbon negative electrode material according to claim 1, characterized in that: The mass content m1 of CaS in the coal-based hard carbon negative electrode material and the mass content m2 of Fe2P in the coal-based hard carbon negative electrode material respectively satisfy 0.01%<m1<0.2%, 0.001%<m2<0.15%, and further preferably satisfy 0.01%<m1<0.035%, 0.001%<m2<0.05%, respectively.
5. The coal-based hard carbon negative electrode material according to claim 1, characterized in that: In coal-based hard carbon negative electrode materials, the element contents shown by ICP are 100-1500ppm Ca, 100-3000ppm Fe, 100-800ppm S, and 10-1500ppm P; More preferably, the element contents shown by ICP are 400-800 ppm for Ca, 800-2000 ppm for Fe, 200-400 ppm for S, and 250-700 ppm for P.
6. The coal-based hard carbon negative electrode material according to claim 1, characterized in that: The first-week reversible capacity of coal-based hard carbon anode materials can reach more than 290 mAh / g, and the first-week coulombic efficiency can reach more than 75%; More preferably, the reversible capacity in the first cycle can reach above 300 mAh / g or above 310 mAh / g, and the coulombic efficiency in the first cycle can reach above 80% or above 83%.
7. The method for preparing the coal-based hard carbon negative electrode material according to any one of claims 1 to 6, comprising the steps of acid treatment, pre-carbonization, steam activation, and secondary carbonization of the coal raw material in sequence; the pre-carbonization is carried out at 700-900°C, and the specific surface area of the material after pre-carbonization is controlled to be >100m 2 / g; after steam activation, the specific surface area of the controlled material increases by 150m 2 / g or more; in the second carbonization process, conversion sources that form CaS and Fe2P with the residual elements are introduced, and the coal-based hard carbon negative electrode material is obtained by carbonization treatment above 1200°C.
8. The method for preparing a coal-based hard carbon negative electrode material according to claim 7, characterized in that: The particle size of the acid-treated coal raw material is Dv50=0.1-20 μm, preferably, the particle size is Dv50=1-10 μm; Preferably, the acid treatment reagent is selected from one or more of hydrochloric acid, nitric acid, and hydrofluoric acid, and more preferably is a mixed reagent of the three, and the volume ratio of the three is more preferably 3:2:5; Preferably, the heating rate of the pre-carbonization is 1-10°C / min; the holding time of the pre-carbonization is 1-48h; steam activation water vapor is used as an activating agent; the temperature of steam activation is 700-900°C; the heating rate of the second carbonization is 1-10°C / min; the holding time is 2-48h; Preferably, the conversion source in the second carbonization includes one or more of a phosphorus source and a sulfur source, preferably NaH2PO2·H2O.
9. The method for preparing a coal-based hard carbon negative electrode material according to claim 7, characterized in that: The specific surface area of the controlled material after steam activation is > 400m 2 / g, and further preferably>500m 2 / g.
10. A sodium ion battery comprising the coal-based hard carbon negative electrode material according to any one of claims 1 to 6.
Citation Information
Cited By
Coal-based hard carbon negative electrode material and preparation method and application thereof
CN120453376A
Method for preparing raw material of hard carbon negative electrode material from bituminous coal
CN120504312A
Method for preparing hard carbon negative electrode material raw material from bituminous coal
CN120504312B